Neurobehavioral Symptoms in Community-Dwelling Adults With and Without Chronic Traumatic Brain Injury: Differences by Age, Gender, Education, and Health Condition - Juengst, Shannon B.; Nabasny, Andrew; Terhorst, Lauren (Frontiers in Neurology, 2019)
Neurobehavioral symptoms after Traumatic Brain Injury (TBI) are prevalent, persist for many years, and negatively affect long-term health, function, and quality of life. Symptoms may also differ based on age, gender, education, race, ethnicity, geographical location, and injury severity. To better understand neurobehavioral functioning after TBI, we need a comprehensive picture of emotional, cognitive, and behavioral symptoms in the context of personal and environmental factors that may affect these symptoms. We collected neurobehavioral symptoms via the self-reported Behavioral Assessment Screening Tool (BAST) in a National Cohort of English (n=2,511) and Spanish-speaking (n=350) community-dwelling adults with and without chronic TBI and other health conditions and a TBI Cohort of English-speaking community dwelling adults (n=218) with a chronic history of documented TBI. The primary focus of the present study was to describe neurobehavioral symptoms in adults with and without TBI, broken down by gender and health conditions and then further by age group or educational attainment. Participants with TBI in the National Cohort reported more symptoms than Healthy Controls and participants in the TBI Cohort. Overall, women reported more fatigue, while men reported more substance abuse and impulsivity. Hispanic/Latinx participants reported more neurobehavioral symptoms than non-Hispanic/Latinx participants across health conditions, though primarily Spanish-speakers reported fewer symptoms than English-speakers, suggesting level of acculturation may contribute to symptom reporting. Neurobehavioral symptoms are more common in chronic TBI than in a neurologically healthy population. However, these symptoms also differ based on personal factors, like age, gender, and ethnicity, and health history.